2016
DOI: 10.3748/wjg.v22.i47.10353
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D differentially regulatesSalmonella-induced intestine epithelial autophagy and interleukin-1β expression

Abstract: AIMTo investigate the effects of active vitamin D3 on autophagy and interleukin (IL)-1β expression in Salmonella-infected intestinal epithelial cells (IECs).METHODSCaco-2 cells, NOD2 siRNA-, Atg16L1 siRNA- or vitamin D receptor (VDR) siRNA-transfected Caco-2 cells were pretreated with 1,25-dihydroxyvitamin D3 (1,25D3), and then infected by wild-type S. typhimurium strain SL1344. The conversion of LC3-I to LC3-II was detected by Western blot analysis and LC3+ autophagosome was analyzed by immunofluorescence. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…Due to the pleiotropic beneficial effects of vitamin D in health and disease, the application of vitamin D as safe dietary supplement is currently discussed as promising option for the adjunct treatment and prophylaxis of various immunopathological morbidities including infectious diseases, intestinal inflammatory conditions, and cancer, for instance (33, 55). In our present vitamin D intervention study applying a clinical acute campylobacteriosis model, prophylactic synthetic 25-OH-cholecalciferol application starting 4 days prior murine infection resulted in dampened C. jejuni induced intestinal and extra-intestinal inflammatory sequalae, but could not lower the high intestinal pathogen loads of more than 10 9 viable C. jejuni per g feces.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the pleiotropic beneficial effects of vitamin D in health and disease, the application of vitamin D as safe dietary supplement is currently discussed as promising option for the adjunct treatment and prophylaxis of various immunopathological morbidities including infectious diseases, intestinal inflammatory conditions, and cancer, for instance (33, 55). In our present vitamin D intervention study applying a clinical acute campylobacteriosis model, prophylactic synthetic 25-OH-cholecalciferol application starting 4 days prior murine infection resulted in dampened C. jejuni induced intestinal and extra-intestinal inflammatory sequalae, but could not lower the high intestinal pathogen loads of more than 10 9 viable C. jejuni per g feces.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of the vitamin D receptor (VDR) on peripheral blood mononuclear cells in the 1980s first pointed to immune-related functions of vitamin D (28, 29). In fact, vitamin D has been shown to be involved in modulating both, innate and adaptive immune responses (3033) and to exert anti-inflammatory effects (34). Furthermore, several reports underline the anti-microbial properties of vitamin D (33).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, biochanin A (BCA), a polyphenolic compound found in certain species of plants, has been proven to target Salmonella infection through AMPK/ULK1/mTOR-mediated autophagy, extracellular traps, and the reversal of SPI-1dependent macrophage M2 polarization (Zhao et al, 2018). In addition, Huang (2016) found that 1,25-dihydroxyvitamin D3 may promote the autophagic removal of intracellular Salmonella and modulate inflammatory responses to prevent the host from the adverse effects of excessive inflammation. Kim et al (2018) evaluated the antibacterial effect of bioprocessed (fermented) rice bran extract (BPRBE) against Salmonella Typhimurium infection, and investigated the mechanisms involved.…”
Section: Certain Drugs Regulate Xenophagy To Combat Salmonella Infectionmentioning
confidence: 99%
“…However, we observed tight binding between VDR and Atg16l1 promotor, leading to low ATG16L1 protein levels in LPS‐tolerant cells, demonstrating negative regulation by VDR on Atg16l1 transcription in LPS‐tolerant cells, which did not change in presence of V D3 . Most effects of VDR on ATG16L1 and autophagy were investigated in epithelial cells (Huang, 2016; Sun, 2016) but not in monocytes/macrophages. Our study focused on the immunosuppression stage in monocytes/macrophages, unlike the parenchyma cells such as epithelial cells which were not immunosuppressed.…”
Section: Discussionmentioning
confidence: 99%